2015
DOI: 10.1155/2015/492050
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Study of Retinal Proteins Associated with Transcorneal Electric Stimulation in Rats

Abstract: Background. To investigate how transcorneal electric stimulation (TES) affects the retina, by identifying those proteins up- and downregulated by transcorneal electric stimulation (TES) in the retina of rats. Methods. Adult Wistar rats received TES on the left eyes at different electrical currents while the right eyes received no treatment and served as controls. After TES, the eye was enucleated and the retina was isolated. The retinas were analyzed by proteomics. Results. Proteomics showed that twenty-five p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…These proteins appear to play various functions (e.g., cellular signaling, synaptic transmission, metabolism, immune function, and structural maintenance) and included several suspected retinal regeneration factors, such as epidermal growth factor receptor (EGFR), prohibitin, tenascin-X, etc. Interestingly, IGF-1, BDNF, and FGF-2 were surprisingly absent from this list, a discrepancy the authors believe is related to their experiments being conducted on wildtype retinas versus a degenerative model 135 , similar to a previous study reporting changes in the transcriptome 124 . Thus, it can be hypothesized that ES treatment may alter the secretion of these neurotrophic factors, resulting in a more balanced and less hostile environment.…”
Section: Application Of Electrical Stimulation To Enhance Cell Transpsupporting
confidence: 55%
See 1 more Smart Citation
“…These proteins appear to play various functions (e.g., cellular signaling, synaptic transmission, metabolism, immune function, and structural maintenance) and included several suspected retinal regeneration factors, such as epidermal growth factor receptor (EGFR), prohibitin, tenascin-X, etc. Interestingly, IGF-1, BDNF, and FGF-2 were surprisingly absent from this list, a discrepancy the authors believe is related to their experiments being conducted on wildtype retinas versus a degenerative model 135 , similar to a previous study reporting changes in the transcriptome 124 . Thus, it can be hypothesized that ES treatment may alter the secretion of these neurotrophic factors, resulting in a more balanced and less hostile environment.…”
Section: Application Of Electrical Stimulation To Enhance Cell Transpsupporting
confidence: 55%
“…In support of this theory, Zhou et al 134 found a positive regulatory effect of ES on the production of BDNF and CNTF in Mμller cells, and also provided evidence that BDNF rather than CNTF may play a major role in the promotion of Mμller cell-induced photoreceptor cell survival. Finally, in a recent proteomic study 135 , TcES performed on wild-type adult Wistar rats was shown to significantly alter the expression of 25 proteins. These proteins appear to play various functions (e.g., cellular signaling, synaptic transmission, metabolism, immune function, and structural maintenance) and included several suspected retinal regeneration factors, such as epidermal growth factor receptor (EGFR), prohibitin, tenascin-X, etc.…”
Section: Application Of Electrical Stimulation To Enhance Cell Transpmentioning
confidence: 95%
“…Electrical stimulation therapy stimulates neurotrophic factors and cell survival pathways by modulating proteins (Kanamoto et al, 2015) and genes (Willmann et al, 2011) involved in cellular signaling, neuronal transmission, metabolism and inflammation (Fig. 7).…”
Section: Electrical Stimulationmentioning
confidence: 99%
“…It was further proposed that the acute changes were direct and transient effects induced by electric shock to neural cells, whereas the chronic changes were indirect and secondary effects in mRNA expression or protein signaling pathways. 17 …”
Section: Improving Vision By Electrostimulationmentioning
confidence: 99%